Hormonal and neuromuscular responses during a singles match in male professional tennis players. - Lopez-Samanes, A. G.; Pallares, J.; Perez-Lopez, A.; Mora-Rodriguez, R.; Ortega, J. F. (PLOS ONE, 2018)
We sought to measure the response of cortisol concentrations around a professional tennis match and its association with hydration status and neuromuscular performance. Nine professional male tennis players were tested in a rest day, and 2-week after, during the first match of a professional tournament played in a clay-court. Salivary concentrations of cortisol (SalCC) were measured in a resting day (9:00 am and 8:00 pm), at the match day (9:00 am and 8:00 pm) and immediately before and after the match. Hydration status was assessed before the match (urine specific gravity; USG) while fluid turnover was tracked during the match. Finally, counter movement jump (CMJ) and handgrip isometric strength (HS) were measured before and after the match. SalCC, either in the morning (P = 0.161) and afternoon (P = 0.683) was similar in rest and match days. However, SalCC increased after the match (P = 0.033). Participants started the match hypohydrated (USG = 1.026±0.002) and during the match lost 1.0±0.3% of body weight despite 1.035±0.124 L/h of fluid ingested. CMJ and HS did not change post-match (P = 0.210 and P = 0.881, respectively). Correlations between the elevations in SalCC and dehydration (% BW loss) during the match were significant (r = -0.632; P = 0.034). Professional male tennis players did not show an anticipatory increase in SalCC the day of the match and neither signs of neuromuscular fatigue after it. During the match, the mild dehydration (i.e., <1.5%) was associated with the increases in cortisol levels which suggests that dehydration may be an added stress to be considered.